2021
DOI: 10.1186/s40345-021-00226-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapy for mood instability within bipolar spectrum disorder: a randomised, controlled feasibility trial of a dialectical behaviour therapy-informed approach (the ThrIVe-B programme)

Abstract: Background A subgroup of those with bipolar spectrum disorders experience ongoing mood fluctuations outside of full episodes. We conducted a randomised, controlled feasibility study of a Dialectical Behavioural Therapy-informed approach for bipolar mood fluctuations (Therapy for Inter-episode mood Variability in Bipolar [ThrIVe-B]). Our study aimed to examine the feasibility and acceptability of a future definitive trial evaluating the clinical and cost effectiveness of the ThrIVe-B programme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…This level of engagement compares favourably to recent comparable trials, e.g. 50% attending at least 50% of mandatory sessions [ThrIVe-B programme (Wright et al 2021 )] and 59% attending 9–10 sessions within 16 weeks [CBT for anxiety in bipolar disorder (Jones et al 2018 )].…”
Section: Discussionsupporting
confidence: 61%
“…This level of engagement compares favourably to recent comparable trials, e.g. 50% attending at least 50% of mandatory sessions [ThrIVe-B programme (Wright et al 2021 )] and 59% attending 9–10 sessions within 16 weeks [CBT for anxiety in bipolar disorder (Jones et al 2018 )].…”
Section: Discussionsupporting
confidence: 61%
“…The two subscales of the DERS that had the strongest associations with recovery were "limited access to emotional regulation strategies" and "non-acceptance of emotional responses", which is in line with previous studies that confirmed the association between emotion regulation and recovery. 39,48 These associations underline the importance of emotion regulation strategies and acceptance of emotions for recovery. These outcomes may inform potential targets for future clinical intervention studies that are aimed at increasing recovery, suggesting that interventions focusing on cultivating openness and acceptance of emotions and the ability to regulate them may be helpful in achieving it.…”
Section: Discussionmentioning
confidence: 93%
“…A DBT-informed program adapted to target inter-episode mood instability in BD (Therapy for Inter-episode mood Variability in Bipolar (ThrIVe-B)) was assessed in an observational feasibility trial (n = 12) and an RCT (n = 43) (Wright et al 2020 ; Wright et al 2021 ). Both trials included adult participants with BD who had experienced several subthreshold hypomanic and depressive episodes over the preceding 2 years.…”
Section: Resultsmentioning
confidence: 99%